Altered expression of glutamate transporter‐1 and water channel protein aquaporin‐4 in human temporal cortex with Alzheimer's disease. (4th March 2018) - Hoshi, A.; Tsunoda, A.; Yamamoto, T.; Tada, M.; Kakita, A.; Ugawa, Y.
Abstract : Aims: Glutamate neurotoxicity plays an important role in the pathogenesis of various neurodegenerative disorders. Many studies have demonstrated that glutamate transporter‐1 (GLT‐1), the dominant astrocytic glutamate transporter, is significantly reduced in the cerebral cortex of patients with Alzheimer's disease (AD), suggesting that glutamate‐mediated excitotoxicity might contribute to the pathogenesis of AD. In a previous study, we have demonstrated marked alterations in the expression of the astrocytic water channel protein aquaporin‐4 (AQP4) in relation to amyloid β deposition in human AD brains. As a functional complex, GLT‐1 and AQP4 in astrocytes may play a neuroprotective role in the progression of AD pathology. However, few studies have examined the correlation between the expression of GLT‐1 and that of AQP4 in human AD brain. Methods: Here, using immunohistochemistry with antibodies against GLT‐1 and AQP4, we studied the expression levels and distribution patterns of GLT‐1 in areas showing various patterns of AQP4 expression in autopsied temporal lobes from eight patients with AD and five controls without neurological disorders. Results: GLT‐1 staining in the control group was present throughout the neocortex as uniform neuropil staining with co‐localized AQP4. The AD group showed a significant reduction in GLT‐1 expression, whereas cortical AQP4 immunoreactivity was more intense in the AD group than in the control group. There were two different patterns of GLT‐1 and AQP4 expression in the AD group: (i) uneven GLT‐1 expression in the neuropil where diffuse but intense AQP4 expression was evident, and (ii) senile plaque‐like co‐expression of GLT‐1 and AQP4. Conclusions: These findings suggest disruption of glutamate/water homoeostasis in the AD brain.